On Citing the Sahidic Version of Hebrews: Theoretical Reflections and Examples from Textual Practice - Malik, Peter (New Testament studies, 2022)
The Sahidic Coptic is one of the earliest and most important versions of the New Testament. Thus, it is essential that its witness be related to the Greek tradition with adequate methodological precision. This article attempts to pave the way for such an undertaking in the Epistle to the Hebrews, a New Testament book which, currently, lacks a major critical edition of its Greek text or an edition of its Sahidic version. Firstly, the present study offers methodological reflections on citing the Sahidic version, with a particular focus on transmissional, editorial, linguistic and translation-technical issues. And secondly, a selection of the most significant variant units in Hebrews is examined with a view to relating the Sahidic evidence to the Greek variant spectrum at each point.